Collisional depolarization of OH(A) with Ar: Experiment and theory. - Brouard, M; Bryant, A; Chang, Y; Cireasa, R; Eyles, C; Green, A; Marinakis, S; Aoiz, F; Kłos, J (2009)
Zeeman quantum beat spectroscopy has been used to measure the 300 K rate constants for the angular momentum depolarization of OH(A (2)Sigma(+)) in the presence of Ar. We show that the beat amplitude at short times, in the absence of collisions, is well described by previously developed line strength theory for (1+1) laser induced fluorescence. The subsequent pressure dependent decay of the beat amplitude is used to extract depolarization rate constants and estimates of collisional depolarization cross sections. Depolarization accompanies both inelastic collisions, giving rise to rotational energy transfer, and elastic collisions, which change m(j) but conserve j. Previous experimental studies, as well as classical theory, suggest that elastic scattering contributes around 20% to the observed total depolarization rate at low j. Simulation of the experimental beat amplitudes, using theoretical calculations presented in the preceding paper, reveals that depolarization of OH(A) by Ar has a rate constant comparable to, if not larger than, that for energy transfer. This is consistent with a significant tilting or realignment of j(') away from j on collision. The experimental data are used to provide a detailed test of quantum mechanical and quasiclassical trajectory scattering calculations performed on a recently developed ab initio potential energy surface of Kłos et al. [J. Chem. Phys. 129, 054301 (2008)]. The calculations and simulations account well for the observed cross sections at high N, but underestimate the experimental results by between 10% and 20% at low N, possibly due to remaining inaccuracies in the potential energy surface or perhaps to limitations in the dynamical approximations made, particularly the freezing of the OH(A) bond.